S-Functionalization of 3, 5-bis(2-pyridyl)-1, 2, 4, 6-thiatriazine: probing the effect of alkyl chain length in the development of tethered materials. (16th February 2017) - Yutronkie, Nathan J.; Tami, Perrine; Singh, Simarpreet; Kleisath, Elizabeth; Gabidullin, Bulat M.; Davis, Rebecca; Brusso, Jaclyn L.
Abstract : The preference of S -alkyl-thiatriazines towards intra vs. intermolecular addition is dependent on alkyl chain length, as demonstrated experimentally and computationally. Abstract : Reactions between 3, 5-bis(2-pyridyl)-4-hydro-1, 2, 4, 6-thiatriazine (Py2 TTAH) and a series of 1, n -dibromoalkanes ( n = 2, 3, 4, 5, 6, 8, 10) were explored and a synthetic route to prepare tethered 3, 5-bis-(2-pyridyl)-1λ 4, 2, 4, 6-thiatriazines is described. When the length of the alkyl group employed is n ≥ 4, S, S ′-alkyl-bis(Py2 TTA) derivatives (8–12 ) are isolated; however, if n < 4, S -cyclopropyl-Py2 TTA (13 ; n = 3) and S -ethenyl-Py2 TTA (14 ; n = 2) are formed due to competitive intramolecular SN 2 cyclization and E2 reactions, respectively. NMR spectroscopy, electron spray ionization mass spectrometry and X-ray crystallography were used to probe the dependence of the alkyl chain length on the reaction pathway. Computational studies are also presented, which support the preference of intramolecular vs. intermolecular SN 2 reactions when n = 3 and n > 3, respectively.